v+(v-16)+3(30-v)=641

Simple and best practice solution for v+(v-16)+3(30-v)=641 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for v+(v-16)+3(30-v)=641 equation:


Simplifying
v + (v + -16) + 3(30 + -1v) = 641

Reorder the terms:
v + (-16 + v) + 3(30 + -1v) = 641

Remove parenthesis around (-16 + v)
v + -16 + v + 3(30 + -1v) = 641
v + -16 + v + (30 * 3 + -1v * 3) = 641
v + -16 + v + (90 + -3v) = 641

Reorder the terms:
-16 + 90 + v + v + -3v = 641

Combine like terms: -16 + 90 = 74
74 + v + v + -3v = 641

Combine like terms: v + v = 2v
74 + 2v + -3v = 641

Combine like terms: 2v + -3v = -1v
74 + -1v = 641

Solving
74 + -1v = 641

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-74' to each side of the equation.
74 + -74 + -1v = 641 + -74

Combine like terms: 74 + -74 = 0
0 + -1v = 641 + -74
-1v = 641 + -74

Combine like terms: 641 + -74 = 567
-1v = 567

Divide each side by '-1'.
v = -567

Simplifying
v = -567

See similar equations:

| 3a+4=24 | | h=32+14t-1+-16t | | -(6x+3)-(-5x-8)=3 | | (9-x)(3x+5)=0 | | -x-18+2x+4=6x+24 | | a-6b+2c+a-6b+n-2c= | | 9y+3=27 | | 4b+25=9b | | 6(4-1)-5(z+8)=16(z+1) | | y=-(1)-3 | | y=-(0)-3 | | y=-(-1)-3 | | 4b+5x=2x | | -8(t-5)-(t+4)=9 | | 2x+10=27 | | 7.7(-9+2x)=-49 | | y=6(5)-8 | | x=9x-12 | | y=6(1)-8 | | 12(2x-5)=24x+16 | | -(3y+2)-(-2y-8)=5 | | y=6(-1)-8 | | 6+2(x-1)=1-3(x-6) | | 4+6(x-2)=1-5(x-1) | | -49=3x+3x-7 | | -(4y+1)-(-3y-6)=4 | | 12+-2a=2 | | 9ln(8x)=54 | | 2y+10(2)=-16 | | 2y+10(-3)=-16 | | -8+2x-4x=-18 | | -5(3n+2)=10 |

Equations solver categories